DYNAMIC CURRICULUM FOR THE EXTRAPOLATION OF INNOVATIVE TEXHNOLOGIES IN FASHION - Ryabchykova, K. (Problems of Engineer-Pedagogical Education, 2018)
The work is devoted to the problem of curricula development for the students of fashion design in the higher educational institutions. Industry constantly faces rapid developments in technologies and implementation of new approaches, what in response distinguishes the necessity of educational system upgrade in order to prepare competent professionals at the end of studies. In close scope was analyzed process of competences’ formation on the example of fashion education in the higher educational institutions. In particular, were discussed expeditious changes and recent innovations, which have introduced 3D technologies and their expanded use in fashion industry, what, as a result, have created necessity to the development of new competences in fashion education. Consequently theory was developed, based on the assumption that competences can be static and dynamic, where dynamic are presented by flexible and steadily reformed disciplines. As the practical implementation, example of 3D technologies usage by students of Ukrainian Engineering Pedagogics Academy was examined. On the basics of analyzed material, were proposed methods of curriculums’ creation, which will allow extrapolation and adoption of continual changes in the industry.